Characterization of the Linker 2 Region in Human Vimentin Using Site-Directed Spin Labeling and Electron Paramagnetic Resonance - Hess, John F. (2006)
Site-directed spin labeling and electron paramagnetic resonance were used to probe residues 281–304 of human vimentin, a region that has been predicted to be a non-α-helical linker and the beginning of coiled-coil domain 2B. Though no direct test of linker structure has ever been made, this region has been hypothesized to be flexible with the polypeptide chains looping away from one another. EPR analysis of spin-labeled mutants indicates that (a) several residues reside in close proximity, suggesting that adjacent linker regions in a dimer run in parallel, and that (b) the polypeptide backbone is relatively rigid and inflexible in this region. However, this region does not show the characteristics of a coiled-coil as has been identified elsewhere in the molecule. Within this region, spectra from positions 283 and 291 are unique from all others thus far examined. These positions, predicted to be in a noncoiled-coil structure, display a significantly stronger interaction than the a–d contact positions of coiled-coil regions. Analysis of the early stages of assembly by dialysis from 8 M urea and progressive thermal denaturation shows the close apposition and structural rigidity at residues 283 and 291 occurs very early in assembly and with a relatively sudden onset, well before coiled-coil formation in other parts of the molecule. These features are inconsistent with hypotheses that envision the linkers as flexible regions, or as looping away from one another, and raise the possibility that the linker may be the site at which dimer alignment and/or formation is initiated. Spin labels placed further downstream yield spectra suggesting that the first regular heptad of rod domain 2 begins at position 302. In conjunction with our previous characterization of region 305–336 and the solved structure of rod 2B from 328–405, the full extent of coiled-coil domain in rod 2B is now known, spanning from vimentin positions 302–405.